Caught in the Middle: A Conceptual Framework for the Antecedents and Outcomes of Work-Family Guilt in Working Mothers from the Perspective of Gender Roles - Merve Gerçek (Sakarya Üniversitesi Kadın Araştırmaları Dergisi)
Although there has been progress in achieving gender equality, working mothers continue to encounter significant challenges balancing work and family roles, leading to work-family conflict (WFC) and subsequent feelings of guilt regarding WFC. Work-family guilt (WFG) is an emotional response to imbalances that arise from the demands of both work and family responsibilities. This study aims to develop a conceptual framework for the antecedents and outcomes of WFG among working mothers, addressing the gap in research regarding their guilt experiences. Drawing on the prior studies, this paper proposes that societal, organizational, and individual factors will interact, leading to WFC and subsequently causing WFG, which in turn results in some undesirable consequences in societal, organizational, and individual domains. Among the existing research on WFC, this study stands out for its comprehensive review of the determiners and consequences of WFG from a gender role perspective. The suggested framework seeks to provide guidance to working mothers, policymakers, managers, and human resource experts on reducing WFG among working mothers, thus enhancing their overall well-being and productivity. This study explores WFG from a gender standpoint, highlighting the significance of employing gender-sensitive strategies for addressing challenges at both individual, organizational, and societal levels.